2005
DOI: 10.1152/ajpregu.00343.2004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary iron restriction modulates hepatic lipid metabolism in the fetuses

Abstract: (TG) concentrations in the fetuses, as well as decreased plasma TG levels in the adult offspring. To investigate how maternal Fe restriction was affecting fetal lipid metabolism, we investigated whether there were changes in liver lipid metabolism in the full-term fetuses. There was a ϳ27% (P Ͻ 0.05) increase in cholesterol but ϳ29% reduction (P ϭ 0.01) in TG concentrations in the liver of the Fe-restricted fetuses. Hepatic mRNA levels of cholesterol 7␣ hydroxylase and liver X receptor-␣ (LXR␣) were reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 57 publications
(53 reference statements)
2
22
0
4
Order By: Relevance
“…However, very little is known about how maternal nutrition may alter cholesterol homeostasis in postnatal life. In one study, maternal dietary iron restriction led to a 21% decrease in fetal growth and an increase in fetal liver cholesterol (21). This was further associated with decreased expression of Cyp7a1 (21).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, very little is known about how maternal nutrition may alter cholesterol homeostasis in postnatal life. In one study, maternal dietary iron restriction led to a 21% decrease in fetal growth and an increase in fetal liver cholesterol (21). This was further associated with decreased expression of Cyp7a1 (21).…”
mentioning
confidence: 98%
“…In one study, maternal dietary iron restriction led to a 21% decrease in fetal growth and an increase in fetal liver cholesterol (21). This was further associated with decreased expression of Cyp7a1 (21). More recently, a LP diet throughout pregnancy in mice was demonstrated to lead to reduced LXR␣ expression at embryonic d 19.5 (22); however the long-term effects of this in utero nutritional insult on cholesterol homeostasis in postnatal life remain elusive.…”
mentioning
confidence: 99%
“…The association seems to also hold true in reverse. Several studies found that reduction of iron by several different methods led to amelioration of adiposity and improvement of obesity and obesity-related diseases (Zhang et al 2005;Fleming and Ponka 2012;Tajima et al 2012; Moreno-Navarrete et al 2014a,b). Unfortunately, the mechanisms of this association between iron and lipid accumulation or obesity remain largely unclear.…”
mentioning
confidence: 99%
“…These offspring also exhibited decreased hepatic and circulating insulin growth factor 1 (Igf-1) which is critical for insulin function, glucose metabolism, and growth [52]. While other models of maternal dietary-induced IUGR led to hypercholesterolemia in postnatal life, uterine ligation appears to have no effect on cholesterol homeostasis unless the offspring were challenged with a high-fat diet in postnatal life [34,53,54]. Although this animal model is physiologically relevant to idiopathic IUGR, it is distinct from dietary-induced undernutrition as it leads to direct decreases in both oxygen and nutrients to the fetus.…”
Section: Uterine Ligation or Ablation Model Of Undernutrition And Lonmentioning
confidence: 99%